Factors Affecting Children's Fear of Milk Tooth Extraction at the Oesapa Health Center, Kupang City: Faktor Yang Mempengaruhi Rasa Takut Anak Terhadap Pencabutan Gigi Susu Di Puskesmas Oesapa Kota Kupang - Darwinto Betty (Poltekkes Kemenkes Kupang, 2020)
Fear in children is an instinct that develops according to the child's development process. This feeling arises through observing an unpleasant object that is instinctively avoided in an attempt to protect itself from harm. This study aims to determine the factors that influence children's fear of milk tooth extraction at the Oesapa Kupang Health Center 2016. The method used in this study is a descriptive method. The population in this study were pediatric patients who were going to have their teeth extracted at the Oesapa Health Center with a total of 70 children. The sample in this study amounted to 70 children. The sampling method used is random sampling (Random Sampling). The results showed that the factors that influenced children's fear of milk tooth extraction at the Oesapa Kupang Health Center with the criteria